2004
DOI: 10.1016/j.femsec.2004.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial diversity in Adélie penguin, Pygoscelis adeliae, guano: molecular and morpho-physiological approaches

Abstract: The total number of bacteria and culturable bacteria in Adélie penguin (Pygoscelis adeliae) guano was determined during 42 days of decomposition in a location adjacent to the rookery in Admiralty Bay, King George Island, Antarctica. Of the culturable bacteria, 72 randomly selected colonies were described using 49 morpho-physiological tests, 27 of which were subsequently considered significant in characterizing and differentiating the isolates. On the basis of the nucleotide sequence of a fragment of the 16S rR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 21 publications
3
18
0
Order By: Relevance
“…The diversity of cultivable bacteria identified in this study was biased toward Gram-negative strains, mostly belonging to the Proteobacteria phylum. This is in good agreement with several previous studies concerning identification of cultivable bacteria from Antarctica (Zdanowski et al 2004(Zdanowski et al , 2013van Dorst et al 2016). Notably, almost 25% of bacterial strains isolated in this study belonged to Actinobacteria phylum, and bacteria representing this group are commonly isolated from Antarctic soils (Smith et al 2006;Zdanowski et al 2013;Cowan et al 2014;Pudasaini et al 2017).…”
Section: Discussionsupporting
confidence: 93%
“…The diversity of cultivable bacteria identified in this study was biased toward Gram-negative strains, mostly belonging to the Proteobacteria phylum. This is in good agreement with several previous studies concerning identification of cultivable bacteria from Antarctica (Zdanowski et al 2004(Zdanowski et al , 2013van Dorst et al 2016). Notably, almost 25% of bacterial strains isolated in this study belonged to Actinobacteria phylum, and bacteria representing this group are commonly isolated from Antarctic soils (Smith et al 2006;Zdanowski et al 2013;Cowan et al 2014;Pudasaini et al 2017).…”
Section: Discussionsupporting
confidence: 93%
“…The CD-ribotypes were closely related to cultured Psychrobacter (Table 4) including the halotolerant, psychrophile Psychrobacter vallis that was isolated from a cyanobacterial mat from the Dry Valleys (Shivaji et al, 2005). Psychrobacter were prevalent in the culturable bacterial community of ornithogenic soil from Eastern Antarctica (Bowman et al, 1996) and have been isolated from penguin guano (Zdanowski et al, 2004). Psychrobacter are obligate or facultative psychrophiles and halotolerant.…”
Section: Bacterial Composition Of the Ornithogenic Soilmentioning
confidence: 95%
“…Zdanowski et al (2004) identified three major phylogenetic groups (Pseudomonadaceae, Flavobacteriaceae and Micrococcaceae) of bacteria found in bird guano at King George Island; however, little is known about the airborne concentrations and dispersion rates of these microorganisms in this region.…”
Section: Aerobiology Of Antarcticamentioning
confidence: 99%